2021
DOI: 10.2166/aqua.2021.123
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of working pressure on water meter registration

Abstract: Fluctuations in the network pressure of water supply systems affect hydraulic performance and water meter accuracy. The development of metering error curves requires steady-state conditions which are extremely rare in water distribution systems characterized by intermittent supply. Simple deterministic models are suggested and developed from monthly data collected over a 4-year period (2010–2014) for three most dominant meter models (Models 1–3) in the Kampala Water Distribution System (KWDS), Uganda. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In view of this study, the age of the water meter is another point to be considered regarding its reading accuracy. Musaazi et al (2021) also had similar findings in another study, which showed that the age of the sensor has a negative correlation with the annual volume read, that is, according to the time the sensor had greater reading errors, errors that remained practically constant after five years. Thus, they suggest that this would be a good time to change the meter in a network for example.…”
Section: Resultssupporting
confidence: 80%
“…In view of this study, the age of the water meter is another point to be considered regarding its reading accuracy. Musaazi et al (2021) also had similar findings in another study, which showed that the age of the sensor has a negative correlation with the annual volume read, that is, according to the time the sensor had greater reading errors, errors that remained practically constant after five years. Thus, they suggest that this would be a good time to change the meter in a network for example.…”
Section: Resultssupporting
confidence: 80%
“…To reach the customer, the pressure is usually kept high at the initial distribution point and must meet a minimum pressure requirement of 1 bar at the customer's endpoint. However, field data shows that the final pressure is less than the provisions and fluctuates [12][13][14]. This condition of course affects the water meter.…”
Section: Introductionmentioning
confidence: 99%